The evolution of fan kingdom: the rising, expansion, and challenges of human brands. Issue 4 (12th September 2016) - Huang, Stephen Chi-Tsun; Huang, Tsui-Ju
Abstract : Purpose: The purpose of this paper is to discuss four main research questions which are as follows: how does a consumer turn into a devoted fan? How does a devoted fan react to the expansion of a human brand? What kind of strategies does a devoted fan take when facing challenges encountered by a human brand? And are devoted fans homogeneous, or can they be further divided into different subgroups? Design/methodology/approach: The basis of grounded theory process is intensive depth interviews with 14 devoted fans of a famous Taiwanese pop singer in a qualitative manner along with content analysis of messages from online fan clubs. Findings: Using the metaphor of kingdom to parallel the phenomenon of fandom, the research also explicates the importance of initial brand position, and the construction and expansion from the core castle – the core positioning of the human brand – to become a kingdom where devoted fans swear to be loyal to the human brand and cross-buy the derivative products of the latter. Five fan's subgroup and a theoretical framework are obtained. Originality/value: The theoretical framework derived in this study explicates how consumers' initial perceptions of the human brand are formed and reinforced and how they become different kinds of fans which in turn influence the strategies they take in the face of the expansion or withdraw of the human brand.